ANALYSIS OF ZOOPLANKTON GENUS COMPOSITION AND ABUNDANCE IN THE WATERS OF LAKE RANAU WARKUK RANAU SELATAN DISTRICT SUMATERA SELATAN PROVINCE - Tiara Santeri Tiara; Septi Hermialingga; Desliana Opie Harliani; Nancy Eka Putri Manurung; Siska Almaniar (Jurnal Perikanan Unram, 2024)
Lake Ranau as a water resource for the community, especially Warkuk Ranau Selatan District, has a fairly high biodiversity. Zooplankton is one of the biological components that functions as an indicator of water quality based on the composition and abundance of zooplankton. This study aimed to analyze the composition of genus and abundance of zooplankton in Lake Ranau, focusing on upstream, midstream, and downstream regions to identify potential differences in zooplankton diversity and density across these areas, potentially influenced by environmental factors such as water quality variation. The data collection method was carried out by sampling surface water and filtered using a plankton net tool. The results showed that the highest genus composition was observed at upstream lake and the highest abundance of zooplankton was found at midstream lake. The results of this study can be concluded that the distribution of zooplankton is not only influenced by biological factors but also by environmental conditions in each location so that the composition and abundance of zooplankton in Lake Ranau varies significantly between the upstream, midstream, and downstream areas.